Place of birth, duration of residence, neighborhood immigrant composition and body mass index in New York City - Park, Yoosun (BioMed Central, 2008)
BACKGROUND: Past research has suggested that changes in culture explain the substantial weight gain seen in many immigrant groups with length of residence in the U.S. and across generations of residence in the U.S. However, it has been theorized that those settling in immigrant and co-ethnic neighborhoods may be buffered against this acculturative process and will be more likely to maintain home country dietary and physical activity patterns. To investigate this theory we incorporated measures of neighborhood immigrant composition into analyses of individual's body mass index (BMI) and generation of immigration and duration of residence in the U.S. METHODS: Multilevel analyses were performed using objectively measured height and weight and survey data on diet and physical activity from a sample of 13,011 residents of New York City. Census data were used to calculate the proportion of foreign-born residents and extent of household linguistic isolation in a ½ mile radial buffer around the subject's home. RESULTS: Foreign birth was associated with a significantly lower BMI (-1.09 BMI units, P < 0.001). This association was weakest among Asians (-0.66 BMI units, P = 0.08) and strongest among Black-Caribbeans (-1.41 BMI units, P = 0.07). After controlling for individual level variables, neighborhood proportion foreign-born was not associated with BMI, but increasing neighborhood linguistic isolation was inversely associated with BMI among Hispanics (-2.97 BMI units, P = 0.03). Furthermore among Hispanics, the association between foreign birth and BMI was stronger in low linguistic isolation neighborhoods (-1.36 BMI units, P < 0.0001) as compared to in high linguistic isolation levels (-0.42 BMI units, P = 0.79). Increasing duration of residence in the U.S. was significantly associated with higher BMI overall and among Hispanics. CONCLUSION: The analyses suggest that acculturation is associated with weight gain, and that neighborhood characteristics are only associated with BMI among Hispanics. However, we suggest that changes in body size currently interpreted as post-migration effects of acculturation to U.S. norms may in fact reflect changes in norms that are taking place internationally.